1965
DOI: 10.1042/bj0940054
|View full text |Cite
|
Sign up to set email alerts
|

RESISTANCE OF ESCHERICHIA COLI TO TETRACYCLINES

Abstract: 1. A strain of Escherichia coli highly resistant to chlortetracycline and partially cross-resistant to tetracycline has been isolated. 2. The nitro-reductase system of the resistant cells was inhibited to a smaller extent by chlortetracycline than was the corresponding enzyme of sensitive cells. 3. The incorporation of leucine in vitro into the ribosomal protein of cell-free preparations from sensitive and resistant cells was equally inhibited by chlortetracycline. 4. Resistant cells accumulated much less chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
1
2

Year Published

1967
1967
1978
1978

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 17 publications
3
43
1
2
Order By: Relevance
“…Several investigators have shown that tetracycline uptake is diminished in resistant strains (3,6,10,17,19). This report deals.…”
mentioning
confidence: 82%
“…Several investigators have shown that tetracycline uptake is diminished in resistant strains (3,6,10,17,19). This report deals.…”
mentioning
confidence: 82%
“…Studies of tetracycline metabolism have demonstrated active uptake ofthe drug into sensitive cells (1,15). However, the amounts of drug taken up by different strains of Escherichia coli did.…”
mentioning
confidence: 99%
“…R-factor-mediated resistance to tetracycline has been shown to involve an altered bacterial permeability to the antibiotic (2,3) and a similar mechanism has been proposed for sulfonamide resistance in gram-negative organisms (8). Up to this time, however, all R-factor-mediated resistance to penicillins and cephalosporins has been thought to involve ,8-lactamase production (12) with a consequent destruction of the antibiotics.…”
mentioning
confidence: 99%